An analysis of the quality differences in black tea produced from various Oolong tea tree cultivars - Shan Huang; Shuyan Li; Yihao Dan; Jiyue Wang; Sunan Shen; Yan Liu (European Journal of Horticultural Science, 2025)
Abstract The Oolong tea plant (Camellia sinensis) possesses distinctive floral and fruity aromas, which enhance the aromatic prominence of processed tea leaves. Its unique flavour profile and quality are highly prized by consumers worldwide. At present, there are few researches on the suitability of black tea. This study used nine oolong tea tree cultivars, including Huangguanyin (HGY), Chunlan (CL), Meizhan (MZ), Jingguanyin (JGY), Jinxuan (JX), Baiyaqilan (BYQL), Rougui (RG), Shuixian (SX) and Taiwaioolong (TWWL), as raw materials for black tea production through an innovative adaptation of traditional processing techniques. The non-volatile components and sensory quality of each tea sample were analysed using determination methods, such as high-performance liquid chromatography (HPLC), along with other relevant analytical evaluations. The results revealed significant differences in the biochemical constituents, including tea polyphenols, caffeine, soluble sugars, free amino acids and other non-volatile components, among the black tea derived from the nine Oolong tea tree cultivars (p < 0.05). The comprehensive total scores of the sensory evaluation ranged between 79.49 and 91.30. The overall aroma of the tea is predominantly sweet and floral, accompanied by a mellow and rich flavour profile. Among the samples, TWWL, BYQL, CL and MZ demonstrated superior taste characteristics, while SX exhibited comparatively inferior taste qualities. The research findings provide theoretical support for the promotion of high-quality black tea varieties and the optimization of processing techniques. Significance of the study What is already known on this subject? Oolong tea tree cultivars are renowned for their distinctive aromatic properties, characterized by pronounced floral notes and fruity undertones. While a diverse array of Oolong cultivars exists, they have been primarily utilized in the production of Oolong tea, with limited exploration of their suitability for black tea processing applications. What are the new findings? In this study, black tea processed from TWWL, BYQL, CL and MZ cultivars exhibited unique flavour characteristics, demonstrating significant differences in both aroma and taste profiles when compared ith traditional large-leaf varieties. What is the expected impact on horticulture? This research has propelled the diversified utilization of oolong tea germplasm resources, established an innovative paradigm for developing premium black tea products with distinctive flavour profiles and contributed to expanding the application domains while enhancing the market competitiveness of horticultural crops.